Imagery and Written Sources of Classical Antiquity and the Problem of Interpretation of Prehistoric European Art - Palaguta, Ilia V. (Actual Problems of Theory and History of Art, 2015)
European cultures of the Neolithic and Copper Age dating back to the 7th–3rd millennia BC present a huge array of art objects, first of all of various forms of small clay sculpture (figurines, miniature models of houses etc.). The idea of connecting the majority of these finds with cults of fertility and the “Great Goddess”, which was confirmed in the 20th century, ought to be rethought. Analysis of antique, particularly Roman material gives close structural analogues to European statuettes of the Neolithic Age. In extant texts groups of gods associated with home and family are mentioned: Genii Familiae, Lares Familiares et Compitales, Penates. Related to them household cults originate from worshipping family or community ancestors. Some features of Lares’ and Penates’ cult and its iconography give grounds to draw a parallel with certain groups of early agriculturalist statuettes, which can be interpreted as images connected with ancestors’ cult. The study of the Bronze Age plastic (III–II millennia BC) also meets important problems. Further studies in the designated area would allow us to reach a new level of interpretation, making the contents of European prehistoric art clear and disclosed.